Increased homocysteine levels in valproate-treated patients with epilepsy: a meta-analysis. Issue 7 (16th July 2014) - Ni, Guanzhong; Qin, Jiaming; Fang, Ziyan; Chen, Yishu; Chen, Ziyi; Zhou, Jueqian; Zhou, Liemin
Abstract : Objective: To determine whether valproate (VPA) monotherapy influences homocysteine metabolism in patients with epilepsy. Design: Systematic review and meta-analysis. Data sources: We searched all articles in English through PubMed, Web of Science and EMBASE published up to August 2013 concerning the homocysteine levels in VPA monotherapeutic patients with epilepsy. Participants: VPA-treated patients with epilepsy (n=266) and matched healthy controls (n=489). Outcome measures: Heterogeneity between studies was assessed using I 2 statistics. Pooled standardised mean difference (SMD) and 95% CIs were calculated using a random effect model. Results: A total of eight eligible studies were enrolled in our meta-analysis. We compared the plasma levels of homocysteine in VPA-treated patients with epilepsy and healthy controls. There was significant heterogeneity in the estimates according to the I 2 test (I 2 =65.6%, p=0.005). Plasma homocysteine levels in VPA-treated patients with epilepsy were significantly higher than in healthy controls under a random effect model. (SMD, 0.62; 95% CI 0.32 to 0.92). Further subgroup analyses suggested that no signiﬁcant differences were present when grouped by ethnicity and age, but the risk of heterogeneity in the West Asian group (I 2 =47.4%, p=0.107) was diminished when compared with that of the overall group (I 2 =65.6%, p=0.005). Conclusions: Our meta-analysis indicates that VPA monotherapy is associated with the increase in plasma homocysteine levels in patients with epilepsy. Whether this association is influenced by ethnicity needs further research.